199k views
0 votes
Y= -3x^2-24x-46 write in vertex form

User Canni
by
4.6k points

1 Answer

6 votes

ANSWER


y= -3{(x + 4)}^(2) + 2

Step-by-step explanation

The given function is:


y= -3x^2-24x-46

Factor -3 for the first 2 terms.


y= -3(x^2 + 8x)-46

We add and subtract the square of the coefficient of x.


y= -3(x^2 + 8x + {(4)}^(2) ) - - 3( {4)}^(2) -46

Factor the perfect square trinomial.


y= -3 {(x + 4)}^(2) ) + 48 -46

The vertex form is:


y= -3{(x + 4)}^(2) + 2

User Mcmac
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.